PERAN DAN TANGGUNG JAWAB PELATIH OLAHRAGA - Muhammad, (Arena, 2010)
Abstract In exercising his profession, coaches have many roles, such as teachers, trainers, drivers, enforcement, discipline, control, community relations officers, planners, fund-raiser, giving advice, and counseling, friends, scientists, and as a student. Coaching style is applied to coach in the coaching process can be categorized into: authoritarian coaches, trainers such as businessmen, nice coach, trainer excited / loud, and coaches are expected to santai.Pelatih ideally behave as follows: (1) instill qualities of character and ideas was done, (2) proper dress in accordance with sessions that were done, (3) have a responsibility to maintain discipline, (4) has the attitude of self-confidence, assertive (assertive), consistent, friendly, honest, and competent, (5) provide initial treatment to the injury suffered by athletes, (6) organize training well, not only on a single practice, but also on programs weekly, monthly, and yearly, and (7) gives the exact reasons for the various things done. In order for coaching to run effective, coaches should have some basic skills include: knowledge, organizing, observing, and analyzing.Keywords: Coach, Sports